Implementasi MIT App Inventor dan Sensor Piezoelectric pada Prototipe Piano berbasis Arduino Mega 2560 - Nimatul Mamuriyah; Amos Girsang (Universitas Internasional Batam, 2022)
Embedded systems that are driven by microcontrollers have been produced so many innovative products in almost all fields including in the field of music. Using this microcontroller makes the products easier to use by the wider community, even though they have never studied it at all. In this study, the piano becomes the object of this study. Design of this Piano prototype was implemented the Arduino Mega 2560 Microcontroller and also the Piezoelectric Sensor. This Piezoelectric sensor has the main function as a tone generator on this Piano prototype, while the Arduino Mega 2560 is the brain of the prototype which will formulate the scale generated by the sensor and store it, Arduino Mega also has a Bluetooth connection facility so that the prototype can be connected to an Android Smartphone with easy. The HC-05 Bluetooth Module has a choice of 2 connectivity modes (receiver and transceiver) and flexibility is realized with the HC-05 Bluetooth Module combined with the MIT App Inventor which allows musicians to be able to choose the song they want to play and that which has been made can be connected to an Android Smartphone device therefore the prototype is equipped with the MIT App Inventor as a visual object for creating applications that can be run on an Android Smartphone. One of the advantages of this prototype is that the user does not need to memorize or understand the score, simply by following the instructions from the LED which will light up according to the tone played. The results of testing and analysis show that the melody sound produced by Prototype Piano can work quite well with the success of an average value of 0.20 Hz and an average error percentage value of 6.88%.